RETRACTED: The Commodification Dilemma: Tourism Pressure and Heritage Conservation in Barcelona - Marina Mazzamuto; Marco Picone (Societies, 2022)
In recent years, the proliferation of tourists in the urban environment has generated several issues in the functioning of cities. As urban tourism has historically been linked to cultural and architectural attractions, this increased tourism pressure has involved and often compromised the common heritage uses. Therefore, many cases saw the implementation of measures that, if on the one hand reduced tourist flows, on the other also drastically restricted the access for residents and totally altered the sense of place in the community. This article explores this topic by applying a Critical Discourse Analysis methodology to the dispute that took place in Barcelona regarding the restricted access to Park Güell. The main results of this work concern the instrumentalisation of both the UNESCO label and participatory processes in the case of Barcelona, along with the failure of regulative measures to solve the problems related to tourism pressure. The article advocates the usage of more qualitative-oriented analyses to address the relationships between urban planning, heritage management and tourism management.